Isogenic Lines: Reaction to the Kazakhstan Population of Stem Rust (Puccinia graminis f. sp. tritici) - Aikerim Ydyrys; Amageldy Sarbaev; Alexey Morgounov; Saltanat Dubekova; Vladimir Chudinov (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
In recent years, intensified development of stem rust of wheat has again been noted in the grain-growing regions of Kazakhstan. To determine the genetic basis of immunity in 2015 – 2019, the authors performed targeted studies in the conditions of the southeast and north of Kazakhstan on the natural and the artificially infectious backgrounds of inoculation. Their scientific novelty consisted in identifying effective Sr genes of wheat resistance to the Kazakhstan population of stem rust. The obtained results of the immunological assessment of the trap varieties show that most studied genotypes with the Sr genes were susceptible to the Kazakhstan population of stem rust. With that, the varieties carrying the Sr31 gene have been affected to varying degrees. It should be especially noted that the Sr31 gene in combination with the Sr24 gene ensured more reliable protection from the population of the stem rust pathogen. The authors have selected the obtained resistance genes by their efficiency: Sr2 complex; Sr11; Sr21; Sr31; Sr36; Sr39; Sr40, SrSatu; SrNin, as well as combinations of the Sr24 and 1RS-Am genes; Sr24.31; Sr6.31.21; Sr6,24,36,1RSAm; Sr7a, Sr12, Sr6; and Sr31 absent. The authors recommend them as sources of resistance to the local stem rust population.